2020
DOI: 10.1177/1073858420975712
|View full text |Cite
|
Sign up to set email alerts
|

Does the Brain-Derived Neurotrophic Factor Val66Met Polymorphism Modulate the Effects of Physical Activity and Exercise on Cognition?

Abstract: The Val66Met is a polymorphism of the brain-derived neurotrophic factor (BDNF) gene that encodes a substitution of a valine (Val) to methionine (Met) amino acid. Carrying this polymorphism reduces the activity-dependent secretion of the BDNF protein, which can potentially affect brain plasticity and cognition. We reviewed the biology of Val66Met and surveyed 26 studies (11,417 participants) that examined the role of this polymorphism in moderating the cognitive response to physical activity (PA) and exercise. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 105 publications
1
13
0
Order By: Relevance
“…Therefore, exercise-induced increase in CTSB levels is a crucial protective factor. Several studies have also found a correlation between a decrease in muscle mass or an increase in body fat percentage and memory loss and cognitive decline (Beeri et al, 2021;Anand et al, 2022;De Las Heras et al, 2022). RT prevents muscle atrophy and increases the expression of muscle secretory factors, exerting a better effect on brain health than other forms of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exercise-induced increase in CTSB levels is a crucial protective factor. Several studies have also found a correlation between a decrease in muscle mass or an increase in body fat percentage and memory loss and cognitive decline (Beeri et al, 2021;Anand et al, 2022;De Las Heras et al, 2022). RT prevents muscle atrophy and increases the expression of muscle secretory factors, exerting a better effect on brain health than other forms of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to remember that we are still relatively naïve as to the role of BDNF in this relationship. In humans, there is inconsistent evidence that this protein [ 41 , 62 ], or the gene that encodes this protein [ 63 ], influences the effects of acute exercise on memory. Furthermore, the specific role of BDNF in explaining the effects of exercise on memory are complicated by the fact that it can only be measured peripherally in humans, so that inferences about the central levels of BNDF are speculative.…”
Section: Controversies and Inconsistencies: Discussion Of Moderatorsmentioning
confidence: 99%
“…In our study, we could not find any association between the BDNF polymorphism with the cognitive response following exercise in young adults. Unfortunately, this observation does nothing but add up to the conflicting evidence on the role of BDNF polymorphism in the exercise–cognition relationship [ 11 ]. Along this line of thought, and in parallel with the findings by de Las Heras, Rodrigues, Cristini, Weiss, Prats-Puig, and Roig [ 11 ], this disparity in the reported results could indicate that, in fact, the cognitive gains associated with physical exercise are not dependent on the genetic profile, and all individuals could derive benefits from exercise on cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the practice of physical exercise has positive effects on cognitive function, with benefits attributed to both acute [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] and chronic exercise [ 2 , 5 , 6 , 7 , 8 , 9 ]. However, there is high variability in the observed effect sizes [ 10 ], which may be explained by the distinct characteristics of the physical exercise design, such as the type or dose, the cognitive domain assessed, or individual differences, such as the genotype [ 11 ]. Moreover, most studies on the relationship between exercise and cognitive function were conducted in children or older adults; meanwhile, adolescent and young adult populations remain underrepresented [ 7 ].…”
Section: Introductionmentioning
confidence: 99%